PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH OLEH INDUSTRI PERTAHANAN PT PINDAD - Arif Tison Situmorang; Djoko Andreas Navalino (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to analyze the empowerment carried out by PT Pindad using descriptive qualitative methods. The results of this study are that PT Pindad has empowered 45 micro and small business partners. The form of empowerment that has been carried out is in the form of training to improve the quality of human resources, providing business capital assistance, and marketing of production results through the participation of UMK in defense industry exhibition events. Currently PT Pindad's TJSL program focuses on the industrial, trade, service and livestock sectors. In the future, this may be devoted to the upstream industry, namely UMK which is engaged in the defense industry so that the UMK products fostered can be directly utilized as a supply chain for PT Pindad in the company's raw materials.